The Revitalization and Preservation of Indigenous Ghanaian Textiles in Contemporary Fashion Design - William, Daitey; Eddy Mary, Takyi; Nathalie, Bonnah (Lafadz Jaya Publisher, 2025)
This study investigates the revitalization and preservation of indigenous Ghanaian textiles in contemporary fashion design, emphasizing their cultural significance, economic potential, and modern challenges. Traditional textiles such as “kente”, “kete”, “adinkra”, and “fugu”/ “batakari” are central to Ghana’s cultural heritage, symbolizing identity and tradition. However, the industry faces hurdles including high production costs, competition from cheaper imports, and diminishing traditional knowledge among younger generations. Adopting a qualitative approach, the research utilized interviews, focus group discussions, and observations involving artisans, fashion designers, educators, and consumers. Findings reveal that despite the immense value of indigenous textiles, their integration into modern fashion is impeded by limited access to raw materials, fluctuating market demand, and inadequate artisan support. Innovative designers, however, are blending traditional textiles with contemporary trends, showcasing adaptability and global appeal. The study recommends strategies such as public education campaigns, financial and technical support for artisans, and stronger intellectual property protections. Promoting sustainable practices, addressing regional production disparities, and fostering designer-artisan collaborations are also key to the industry’s sustainability. This research underscores the role of Ghanaian textiles in economic empowerment and cultural preservation, advocating for a balanced approach that merges tradition with modern innovation to ensure global relevance and sustainability.